Integrative analysis and validation of dysregulated long non‐coding RNAs in colon cancer. Issue 4 (20th January 2020) - Zhang, Qun; Bian, Yinzhu; Zhu, Yiping; Wan, Li; Kong, Linghui; Hu, Jing; Yang, Mi; Li, Li; Liu, Baorui; Qian, Xiaoping
Abstract: It is an increasing evidence that long non‐coding RNAs (lncRNAs) are involved in tumour initiation and progression. Here, we analysed RNA‐sequencing data from the Cancer Genome Atlas (TCGA) datasets. Totally, 1176lncRNAs, 245miRNAs and 2081mRNAs were identified to be differentially expressed (DE) in colon cancer tissues compared with normal tissues. CASC21, a novel lncRNA located in 8q24.21 locus, was significantly overexpressed in 30 colon cancer tissues compared with matched normal tissues by qRT‐PCR assay. CASC21 tended to higher expression as the increase of the tumour‐node‐metastasis (TNM) classification. Functionally, CASC21 promoted cell proliferation by regulating cell cycle and enhanced tumour metastasis by epithelial‐mesenchymal transition (EMT) in colon cancer. Mechanism study indicated that CASC21 might be involved in activating WNT/β‐catenin pathway in colon cancer. In addition, we also built a competing endogenous RNA (ceRNNA) network by bioinformatic analysis using TCGA datasets. Together, our results not only provide novel lncRNAs as potential candidates for further study but also prove that CASC21 is an oncogenic regulator through activating WNT/β‐catenin signalling in colon cancer.